Ethnomathematics Exploration at Deli Serdang Museum - Donni Arfianda; Hasrat Bohalima; Siti Khayroiyah (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
Mathematics and culture are two things that cannot be separated because the application of mathematics is always applied in everyday life. Culture can be used as a source of learning for students in schools. Mathematics related to culture is called ethnomathematics. The Deli Serdang Museum, located on Jalan Petapahan, Lubuk Pakam District, Deli Serdang Regency, is one of the historical places in Deli Serdang. The purpose of this study is ethnomathematics. An ethnomathematics study at the Deli Serdang Museum was conducted. This study conducted qualitative research using an ethnographic approach. Data were collected directly by researchers through observation, interviews, documentation, and literature studies. Based on the research, researchers obtained several mathematical concepts, such as flat buildings and spaces at the Deli Serdang Museum. The results of the investigation at the Deli Serdang Museum showed that mathematical concepts include flat quadrilateral buildings, such as rectangles, squares, or trapezoids, as well as flat curved-sided buildings in the form of circles and cylinders. The results of the exploration of the Deli Serdang Museum showed mathematical concepts such as flat buildings and spatial buildings. Researchers discovered the concept of quadrilateral plane shapes, such as rectangles, squares, and trapezoids, as well as curved-sided plane shapes in the form of circles and cylinders.